Human Error Analysis to Minimize Work Accidents Using the HEART and SHERPA Methods at PT. Wonojati Wijoyo: Analisis Human Error untuk Meminimalkan Kecelakaan Kerja dengan Menggunakan Metode HEART dan SHERPA di PT. Wonojati Wijoyo - Noventya Cahyani, Salma; Safirin, M. Tutuk; Donoriyanto, Dwi Sukma; Rahmawati, Nur (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2022)
PT Wonojati Wijoyo is a company that produces furniture for export. In carrying out the production process, work accidents often occur. One of the causes is the factor of human negligence. Work accidents that have occurred include torn wounds due to being hit by a machine, legs hit by wood to make them swollen, fingers hit by machines to open wounds, fingers caught in blocks to open wounds. This study aims to determine the value of Human Error Probability (HEP) and recommend improvement strategies for activities that have the potential to cause human errors to minimize work accidents. The method used in the analysis of human error is the HEART method and the SHERPA method. The results showed that there are critical activities that have the potential for human error to occur, namely in 14 subtasks of 9 processes. The highest probability of human error is in the subtask of cutting wood plates using a circle machine with a HEP value of 0.88827 including the high category. While the lowest probability of human error is in the subtask of setting a copy machine with reference wood with a HEP value of 0.00372 including the medium category. One of the recommendations for improvement strategies to minimize work accidents is that the company needs to conduct training on K3 on a scheduled basis with an explanation of the risks that occur if you do not use Personal Protective Equipment (PPE).